Military Operations Other Than War in Maintaining Security and Peace from Armed Separatist Criminal Group in Papua - Cahyadi, Cecep; Herdiansah, Ari Ganjar; Djuyandi, Yusa (International Journal of Psychosocial Rehabilitation, 2020)
-TPN-OPM as KKSB in Papua aims to fight for independence and establish its state separate from the Republic of Indonesia. TPN-OPM carried out its movement through criminal acts as well as demand justice through international diplomacy. This study tries to analyze how MOOTW in maintaining security and peace from TPN-OPM in Papua by Kopassus TNI-AD. This study employs a descriptive analysis method with a specific data collection gained through interviews, observation, and library research with both method and source triangulation to validate the findings of this study. This study found out that MOOTW implementation by Kopassus obtained through an effective operation with various approaches such as social, humanity, political, economic, and educational to improve the welfare and equitable development of the people in Papua as well as solving the causes of separatist movement to the root. This study also examines the challenges that arise are the overlapping duties between Kopassus TNI-AD and National Police, to accelerate the national security from TPN-OPM threat, the government must have a clear legal framework for Satgas Kopassus TNI-AD to operate together with Polri.